Pengembangan Media Android Augmented Reality Smart Card (AARSC) Untuk Meningkatkan Keterampilan Berpikir Kreatif Dan Hasil Belajar IPS Peserta Didik Sekolah Dasar - Putri Novia Rahmawati; Yatim Riyanto; Nasution (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
This study aims to describe the validity, practicality, and effectiveness of Android Augmented Reality Smart Card (AARSC) Media in improving creative thinking skills and learning outcomes of fourth grade elementary school students. The methods used are Research and Development and ADDIE model Analysis (Analysis), Design (Design), Development (Development), Implemetation (implementation), and Evaluation (evaluation). The method of data retrieval is done by validation, observation, test, and questionnaire. The results showed that the validity of AARSC media obtained a percentage of validity of 86% (very valid). The practicality of AARSC media in terms of learning implementation obtained 91.42% (very good) and in terms of student responses obtained 87% (very practical). The effectiveness of AARSC media obtained from (1) cognitive, namely paired t-test get the result that there is a significant difference between the average results of understanding of learners and n-gain increased 0.63 medium criteria; (2) during the learning conducted in 2 (two) meetings, the attitude of the learners has increased; (3) creative thinking skills get very effective results, namely 81%. The results have been obtained, it can be concluded that the developed media is said to be very feasible as a learning medium